Analisis Fundamental Saham Terhadap Pertumbuhan Saham pada PJ Metal Tahun 2019-2023 - Jeon SukJa; Muhani (P3M Politeknik Negeri Banjarmasin, 2024)
This research aims to analyze the impact of stock fundamentals on stock growth at PJ Metal. PJ Metal has experienced an increase in its financial reports over the past 5 (five) years. Despite an increase in debt, total assets and equity (capital) have also continued to grow. Based on the income statement, it can be seen that the sales growth rate in 2021 reached 92%, which is the highest growth rate. The liquidity ratio measures the company’s ability to pay short-term debt. PJ Metal’s liquidity ratio is above 100%, indicating good liquidity. The leverage ratio measures how much debt the company has compared to its equity. PJ Metal’s leverage ratio is around 50%, which is considered reasonable. However, this leverage ratio is still lower compared to other Korean companies that have higher debt levels. The activity ratio describes how efficiently the company utilizes its assets. Although PJ Metal’s activity ratio decreases every year, the figures are still within the normal range. The profitability ratio includes ROE (Return on Equity) and ROA (Return on Assets). PJ Metal has performed well in both of these ratios, except in 2023. The market value ratio shows that PJ Metal’s earnings per share (EPS) have increased. Based on these financial reports, PJ Metal’s total assets and equity continue to increase despite the decline in PJ Metal’s stock price. Based on this fundamental analysis, it is expected that PJ Metal’s stock price may increase in the future.